Homozygous 2bp Deletion in the Human Factor VII Gene: A Non-Lethal Mutation that Is Associated with a Complete Absence of Circulating Factor VII - Peyvandi, Flora; Mannucci, Pier M.; Jenkins, P. Vince; Lee, Anselm; Coppola, Raffaella; Perry, David J. (Thrombosis and Haemostasis, 2000)
We report the case of a 5-year-old boy with severe factor VII deficiency. The affected child presented at the age of 8 months and again at 18 months with bleeding from the gastrointestinal tract but the diagnosis of factor VII deficiency was not made until the age of 3 years. He was treated with fresh frozen plasma and subsequently factor VII concentrates and to date remains well. To identify the causative mutation, the factor VII gene was screened by SSCP and direct sequence analysis. A single homozygous 2bp deletion (-CT) mutation was identified in exon 1a removing nucleotides 27/28 (codons 52/53). Both parents, who were first cousins, were heterozygous for the mutation. The mutation located in the prepropeptide of factor VII, results in a complete absence of factor VII in plasma. This case indicates that a complete absence of plasma factor VII is not necessarily a lethal condition.
Keywords: FVII; mutation; deletion